Concept Analysis of Recovery in Nursing: - Safa, Azade; Adib-Hajbaghery, Mohsen (Galen Medical Journal, 2021)
Recovery is an abstract multidimensional concept. There is no clear definition for recovery because this concept has specific meanings for individuals. This study aimed to analyze the concept of recovery in nursing. A concept analysis was conducted using Walker and Avantâ€™s method. An extensive literature review was conducted. The primary search key terms were â€œrecovery,â€ â€œconcepts related to recovery,â€ and â€œnursing.â€ The publication date was limited to 2006â€“2019. Data related to the definitions, attributes, antecedents, and consequences of recovery were extracted from the reviewed studies. We found several attributes for this concept. Physical attributes of recovery included fighting with illness, experiencing an injury, and pain. Mental attributes were achieving self-restoration, hopefulness, self-confidence, self-identity, the meaning of life, and personal growth. Social attributes were self-determination, autonomy, support, social confidence, and active participation in social relationships. The antecedents and consequences of recovery were classified into physical, mental, and social dimensions. Model, borderline, and contrary cases were presented. Recovery is a complex and dynamic process, which is unique to individuals based on their characteristics and conditions. [GMJ.2021;10:e2164]